Trifascicular block in patient with acute coronary syndrome - Carlos Rafael Almira-Gómez; David Armando Guach-Hevia; Lilian Beatriz Rosales-Pupo (Universidad Médica Pinareña, 2020)
Introduction: prolongation of the QRS complex due to complete and incomplete blockages of the left branch of the His bundle is an important predisposing factor for systolic heart failure. Cardiac resynchronization therapy that includes the use of an implantable cardiac device can provide clinical benefit for patients suffering from these pathologies.